Artificial light at night reverses monthly foraging pattern under simulated moonlight. (27th July 2022) - Tidau, Svenja; Whittle, Jack; Jenkins, Stuart R.; Davies, Thomas W.
Abstract : Mounting evidence shows that artificial light at night (ALAN) alters biological processes across levels of organization, from cells to communities. Yet, the combined impacts of ALAN and natural sources of night-time illumination remain little explored. This is in part due the lack of accurate simulations of the complex changes moonlight intensity, timing and spectra throughout a single night and lunar cycles in laboratory experiments. We custom-built a novel system to simulate natural patterns of moonlight to test how different ALAN intensities affect predator–prey relationships over the full lunar cycle. Exposure to high intensity ALAN (10 and 50 lx) reversed the natural lunar-guided foraging pattern by the gastropod mesopredator Nucella lapillus on its prey Semibalanus balanoides . Foraging decreased during brighter moonlight in naturally lit conditions. When exposed to high intensity ALAN, foraging increased with brighter moonlight. Low intensity ALAN (0.1 and 0.5 lx) had no impact on foraging. Our results show that ALAN alters the foraging pattern guided by changes in moonlight brightness. ALAN impacts on ecosystems can depend on lunar light cycles. Accurate simulations of night-time light cycle will warrant more realistic insights into ALAN impacts and also facilitate advances in fundamental night-time ecology and chronobiology.